AN OVERVIEW OF STRICT LIABILITY OFFENCES AND CIVIL PENALTIES IN THE UK’S ENVIRONMENTAL LAW - Mahfud, Mahfud (Jurnal Hukum dan Peradilan, 2020)
The UK has incorporated the strict liability principle in dealing with the environmental offence in its legislations. However, the principle application has some detrimental impacts. This article aims to discuss strict liability crimes in the UK’s environmental legislations and civil penalties in the UK, the detrimental effects of applying its principle and the reasons for supplementing criminal penalties for environmental offences with civil penalties. This will be done through the adoption of a doctrinal legal research method. The incorporation of strict liability principle in the UK’s legislations can be found in the Environmental Protection Act 1990, the Water Resources Act 1991, Part 2A of the Environmental Protection Act 1990 and the Environmental Permitting (England and Wales) Regulations 2010 (SI 2010 No. 675). The detrimental effects of the principle application are the ignorance of mens rea element, unfair trial, ineffective environmental damage prevention, and contradictory to release right. The reasons for applying civil penalties of criminal law violation in regard with violating environmental law are this punishment is possible to be imposed on companies, it strengthens another kind of non-criminal sentence sanction, it is a peaceful solution, a polluter may manage by himself to repair the damage, it has no stigma on the polluter and it has wider law enforcement form. There is a dearth of literature looking at the latest UK’s legislation incorporating strict liability principle application. This article will fill this literature gap.